Pengaruh Edukasi Kesehatan Penggunaan Video Terhadap Pengetahuan Ibu Tentang Komplikasi Kehamilan Di Uptd Puskesmas Kwandang - Ernawati, Ernawati; Kue, Sri Nuraini (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Efforts to increase awareness Mother pregnant for do inspection is with increase his knowledge, one of method increase knowledge somebody with method give Education health. Education health aiming for educate public about health. This involves various aspect like health environmental, physical, social, mental, emotional, intellectual, and health reproduction (Rianti, 2021). Research purposes know Influence Health Education Using Videos On Mother's Knowledge About Complications Pregnancy In Upd Health Center Kwandang.Method study with pretest and posttest. Type of test with using the T test. Population 35 people, sample 35 people with total sampling method. The results of the above study can be seen that the average mother's answer before being given health education was 51.43 with a standard deviation of 9,745 and after being given health education the average mother's answer was 98.86 with a standard deviation of 4,710. Statistical test results P-Value 0.001 < α 0.05. So it can be concluded that there is an effect of health education on the knowledge of pregnant women about how to complicate pregnancy. The researcher assumes that health education through video has a positive influence on maternal knowledge about pregnancy complications. Researchers assume that well-designed, informative, and easy-to-understand health education videos can improve mothers' understanding of various pregnancy complications, such as preeclampsia, bleeding, and infection. We also assume that videos can encourage mothers to be more proactive in monitoring their pregnancy health. As for the suggestions that are expected from results study This among others are: The need for increase socialization about factors that influence Complications Pregnancy. Educational institutions are expected add references and sources reading about influence Complications Pregnancy, and for researcher furthermore to develop other variables that influence​ Complications Pregnancy.